Relationship between Interleukin-6 Expression with the Progressive and Severity of Ulcerative - Arif Nur Widodo; Neneng Ratnasari; Siti Nurdjanah (Faculty of Medicine Universitas Gadjah Mada, 2019)
Background. Based on international statistics, the incidence of Inflammatory Bowel Disease (IBD) is about 2.2-14.3 cases per 100.000 people per year for Ulcerative Colitis (UC). In Indonesia, there is no epidemiological study of IBD. To assess the degree of severity associated with the ulcerative colitis disease can be used a varietyof tools, including the Truelove Witts score which has sensitivity and specificity that high enough for UC in the phase of active disease. Interleukin-6 (IL-6) is a pro-inflammatory cytokine that plays a very important role in the self-defense mechanism and acts as an acute-phase protein. Serum levels of IL-6 and increased expression in the colonic mucosa of active IBD patients indicate the level of IBD disease activity.Aims. The aim of the study was to determine the relationship between Interleukin-6 expression (IL-6) and the severity of UC disease using Truelove Witts classification.Methods. This study used a cross-sectional method that analyzed the relationship between IL-6 expression and UC weighing based on Truelove Witts classification using colon tissue biopsy results from UC patients who met inclusion and exclusion criteria.Results. Th ere were 26 subjects studied and performed an endoscopic analysis and anatomical pathology. Mean age of research subjects were 52.73 + 11.11 years with men's favored subjects (n = 15). Subjects were severe UC 16 (61.5%), moderate 7 (26.9%) and mild 3 (11.5%). More male subjects in mild UC, 12 vs. 3 and more female subjects in moderate-severe UC, 4 vs. 7 (p 0.032). Signifi cant diff erences in IL-6 expression in defecation were > 4 times/day, IL-6 300 (285-400) versus defecation < 4 times/day, IL-6 295 (212.1-340) p 0.039. Signifi cant diff erence in IL-6 expression between mild UC 295 (212.1-340) with moderate- severe UC 301.66 (235.57-400) with p value 0.032.Conclusion. IL-6 expression in moderate-severe UC subjects was higher than mild UC subjects based on Truelove Witts criteria.Keywords: Inflammatory Bowel Disease, Ulcerative Colitis, Truelove Witts classification, Interleukin-6.